PENGARUH MODEL PEMBELAJARAN BLENDED COOPERATIVE E-LEARNING TERHADAP HASIL BELAJAR, SELF-EFFICACY DAN CURIOSITY SISWA DALAM PELAJARAN FISIKA DI SMA NEGERI 1 PALU - Untara, Ketut Alit Adi (JSTT, 2014)
The objective of this research was to find out the influence of learning of blended cooperative e-learning in self efficacy and curiosity of the physics student in SMA Negeri 1 Palu. The sampel were 82 students, 44 were for experiment class and 38 for control class. The data was taken by using questionnaire, written test of observation and documentation. The primary data was taken by using self-efficacy questionnaire was used to take the response of students’ confidence, while the curiosity questionnaire was used to take the responds of the students’ curiosity from the influence of the learning of blended cooperative e-learning whereas the written test used to take the students’ learning outcome data. Observation sheet and documentation was used as the supporting data. The primary data processing was by done using t-test of average through statistical analysis and service solution. Sig score used was (sig) 0,05. From the research result, it was concluded that: 1) there was a significance influence of the learning application of blended cooperative e-learning toward students’ self-efficacy and curiosity, 2) there was a significance of learning application of blended cooperative e-learning toward students’ learning outcome